2010
DOI: 10.1007/s11663-010-9380-6
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Measurement Deviation during Annealing of Multiphase Steels

Abstract: A pyrometric analysis of the temperature of continuous annealed strip material is an essential component of industrial production. However, despite calibration, the development of composition-dependent oxides during annealing prevents an accurate pyrometric measurement of actual strip temperature. An Al-based and a Si-based transformation induced plasticity (TRIP)-assisted steel were pyrometrically analyzed during annealing under a reducing atmosphere (5 pct H 2 and 95 pct Ar). Oxide development on both steels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…Various studies have examined how evolving radiative properties may lead to pyrometry errors, with a particular focus on surface oxides during annealing. Thiessen et al [ 10 ] observed variations between thermocouple and pyrometric temperature measurements of transformation‐induced plasticity (TRIP) steel samples when annealed in a reducing atmosphere of 95% Ar and 5% H 2 ; these differences were attributed to emissivity changes caused by the formation of surface oxides during annealing. Somveille et al [ 9 ] also showed how oxidation of DP DP‐780 and 980 steels during annealing may influence emissivity and pyrometric temperature measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have examined how evolving radiative properties may lead to pyrometry errors, with a particular focus on surface oxides during annealing. Thiessen et al [ 10 ] observed variations between thermocouple and pyrometric temperature measurements of transformation‐induced plasticity (TRIP) steel samples when annealed in a reducing atmosphere of 95% Ar and 5% H 2 ; these differences were attributed to emissivity changes caused by the formation of surface oxides during annealing. Somveille et al [ 9 ] also showed how oxidation of DP DP‐780 and 980 steels during annealing may influence emissivity and pyrometric temperature measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Many methods have been developed to mitigate pyrometer errors caused by uncertain spectral emissivity [2][3][4][5][6][7]. Whenever possible, pyrometers are aimed at the notch formed between the steel strip and the roll to exploit the blackbody cavity effect [2].…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, this method is sensitive to misalignment and any temperature difference between the strip and the roll; moreover, many key points in steel production do not facilitate this type of measurement. Dual-and multi-spectral measurements are also often used to mitigate the impact of uncertain radiative properties [3][4][5][6][7]. In two-color pyrometry (a version of dual-spectral pyrometry), the ratio of the spectral emissivity at the two detection wavelengths is assumed to be constant and known.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It might be within the semiconductor industry [6] or for materials that readily oxidize in an oxygen containing atmosphere [3], [7]. The motivation for the development of the ECSP temperature measurement method was the inability to predict the emissivity changes for a Ti6Al4V-specimen subjected to thermal processing [3].…”
Section: Introductionmentioning
confidence: 99%